Lines, faces and surgical masks: drawings in SARS-CoV-2/ Covid-19 pandemic (Revista Apotheke, 2024)
The Covid-19 pandemic covered faces with protective masks, of different shapes and typologies, which transformed the visibility of human facial expressions. The observational drawings presented here are snapshots of this reconfiguration, carried out in Lisbon in 2020, during my daily life during the pandemic. Quick notes of strangers in public spaces, recorded in situ, in notebooks or loose sheets, with materials I had at hand (or in my pocket). The line’s simplicity allowed the recording speed’s urgency to reduce the embarrassment of ocular fixation, in a vulnerable public health context. The geometric modelling of the mask broke with the canon of proportions and changed the expression and the minimum elements of facial recognition. The eyes-nose-lips compositional relationship disappeared, to give way to other entities: gaze-eyebrow, forehead trapezium, hair frame, ears-hanger, and neck-pedestal. In the new visual order, the conflict between identity and abstraction has awakened the symbolic, social and cultural values of the use of masks in the construction of personality, the representation of narratives and the oppression of rights and freedoms.
Keywords: drawing; face; identity; visual expression; Covid-19 Pandemic